2010
DOI: 10.1007/s11218-010-9147-6
|View full text |Cite
|
Sign up to set email alerts
|

Against the odds: academic underdogs benefit from incremental theories

Abstract: An implicit theory of ability approach to motivation argues that students who believe traits to be malleable (incremental theorists), relative to those who believe traits to be fixed (entity theorists), cope more effectively when academic challenges arise. In the current work, we integrated the implicit theory literature with research on top dog and underdog status to predict self-efficacy in an academic context. To examine our predictions, we assessed college students' (N = 165) implicit theories of mathemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 56 publications
4
28
0
Order By: Relevance
“…This idea stems from by Davis, Burnette, Allison and Stone (2010) who observed that a growth mindset was key when students, in a mathematical competition, believed that they were less capable than the rest of their peers. Also, Chen and Pajares (2010) point out that a growth mindset is important when students begin to lower their performance, so future research could analyze whether this intervention would be more effective in students who have seen their Academic performance or with immigrant students since the risk of school failure is higher (Sandín-Esteban and Sánchez-Martí, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This idea stems from by Davis, Burnette, Allison and Stone (2010) who observed that a growth mindset was key when students, in a mathematical competition, believed that they were less capable than the rest of their peers. Also, Chen and Pajares (2010) point out that a growth mindset is important when students begin to lower their performance, so future research could analyze whether this intervention would be more effective in students who have seen their Academic performance or with immigrant students since the risk of school failure is higher (Sandín-Esteban and Sánchez-Martí, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we examined associations across a range of disciplines, including school psychology (e.g., Doron et al, 2009), health psychology (e.g., Burnette, 2010), sports psychology (e.g., Ommundsen, 2003), developmental psychology (e.g., Bempechat, London, & Dweck, 1991), STEM-related fields (e.g., women in math; Davis, Burnette, Allison, & Stone, 2011), leadership studies (e.g., Hoyt, Burnette, & Innella, 2011), organizational behavior (e.g., Maurer et al, 2003), and neuroscience (e.g., Mangels et al, 2006). Thus, results are not only applicable to diverse contexts and populations, but also to a broad array of fields and subfields of psychology.…”
Section: The Present Reviewmentioning
confidence: 99%
“…They have also been shown to be associated with other constructs including academic motivation (Ommundsen et al 2005), cognitive engagement (Dupeyrat and Mariné 2005), learning and achievement goals (Blackwell et al 2007;Dinger and Dickhäuser 2013), epistemic beliefs and goal orientations (Chen and Pajares 2010), selfefficacy (Chen and Pajares 2010;Davis et al 2011), and self-regulated learning (Burnette et al 2013;Greene et al 2010). While clearly an important framework, an alternative position on implicit theories exists with respect to the 'prototypical' nature of intelligence.…”
Section: Implicit Theories Of the Prototypical Nature Of Intelligencementioning
confidence: 99%